Positive electrode active material for lithium-ion batteries

The lithium-nickel-cobalt-manganese-containing composite oxide positive electrode active material, with specific structural and compositional relationships, addresses the high initial resistance and increased resistance issues in lithium-ion batteries, achieving improved durability and low resistance levels.

JP7655686B2Active Publication Date: 2025-04-02TOYOTA JIDOSHA KK +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022022816
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-17
Publication Date
2025-04-02
Estimated Expiration
2042-02-17

AI Technical Summary

Technical Problem

Lithium-ion batteries using positive electrode active materials from existing patents exhibit high initial resistance and increased resistance with repeated charge and discharge cycles.

Method used

A positive electrode active material made of lithium-nickel-cobalt-manganese-containing composite oxide, with secondary particles formed by aggregating primary particles, and specific compositional and structural relationships defined by equations (1) and (2) to optimize crystal structure stability and lithium occupancy.

Benefits of technology

The proposed active material achieves lower initial resistance and suppresses resistance increase during repeated charge and discharge cycles, enhancing durability and maintaining low resistance levels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655686000003
    Figure 0007655686000003
  • Figure 0007655686000004
    Figure 0007655686000004
  • Figure 0007655686000001
    Figure 0007655686000001
Patent Text Reader

Abstract

To provide a positive electrode active material for a lithium ion battery, which is low in initial resistance, and which is arranged so that the increase in resistance in the case of charge and discharge operations being repeated can be suppressed.SOLUTION: A positive electrode active material for a lithium ion battery comprises a composite oxide containing lithium, nickel, cobalt and manganese. The positive electrode active material includes a secondary particle produced by agglomeration of primary particles. The positive electrode active material satisfies the relation given by the following expression (1) and (2): (18.768-a) / b≤0.0024 (1) and c / d≤2.66 (2), provided that in the expression (1), "a" is a peak top of (003) plane of the positive electrode active material measured by X-ray diffraction, and falls in a range of a<18.768, and "b" is a mole number of manganese to a total mole number of the nickel, cobalt and manganese in the positive electrode active material and in the expression (2), " c" is a width of 1 / 20 of "a" and "d" is a half-value width of "a".SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to positive electrode active materials for lithium ion batteries. [Background technology]

[0002] Lithium-ion batteries are widely used as portable power sources for personal computers, mobile terminals, etc., and as vehicle power sources for electric vehicles, hybrid vehicles, etc. In particular, there is a demand for higher capacity lithium-ion batteries as vehicle power sources.

[0003] A lithium ion battery includes a positive electrode, a negative electrode, an electrolyte, etc. The positive electrode includes a positive electrode active material layer and a positive electrode substrate. In order to realize a high capacity lithium ion battery, it has been proposed to use a lithium transition metal composite oxide as a positive electrode active material (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-107536 A [Patent Document 2] Patent Publication No. 2021-51880 Summary of the Invention [Problem to be solved by the invention]

[0005] However, lithium ion batteries using the positive electrode active materials disclosed in Patent Documents 1 and 2 have problems in that they have high initial resistance and that the resistance increases with repeated charging and discharging.

[0006] Therefore, an object of the present disclosure is to provide a positive electrode active material for a lithium ion battery that has a low initial resistance and is suppressed from increasing in resistance during repeated charging and discharging. [Means for solving the problem]

[0007] [1] The present disclosure relates to a positive electrode active material for a lithium ion battery, comprising a lithium nickel cobalt manganese-containing composite oxide, The positive electrode active material includes secondary particles formed by agglomeration of a plurality of primary particles, The positive electrode active material has the formula (1): (18.768-a) / b≦0.0024 (1) and equation (2): c / d≦2.66 (2) Fulfilling the relationship, In the formula (1), a is the peak top of the (003) plane measured by X-ray diffraction of the positive electrode active material, and is in the range of a<18.768; b is the number of moles of manganese relative to the total number of moles of nickel, cobalt, and manganese in the positive electrode active material, In the formula (2), c is 1 / 20 of the width of a, d is the half width of the a; Cathode active material.

[0008] According to the new findings of the present disclosure, when the positive electrode active material satisfies the relationship between the above formulas (1) and (2), it is expected that the initial resistance can be reduced and an increase in resistance during repeated charge and discharge can be suppressed.

[0009] That is, the closer the value of the peak top is to 18.768, the more uniformly the transition metal (nickel, cobalt and manganese) is dispersed in the transition metal layer (nickel, cobalt and manganese) in the crystal structure of the lithium nickel cobalt manganese-containing composite oxide, and the higher the occupancy rate of lithium in the lithium layer. On the other hand, the peak top is affected by the composition ratio of the transition metal, particularly the composition ratio of manganese. Therefore, formula (1) is defined as an index representing the value of the peak top that removes the influence of the composition ratio of manganese in the transition metal. Since the crystal structure of the lithium nickel cobalt manganese-containing composite oxide that satisfies formula (1) is stable, it is considered that durability is improved and an increase in resistance is suppressed even when charging and discharging are repeated. In addition, since the transition metal is uniformly dispersed in the transition metal layer of the positive electrode active material layer and a large amount of lithium is present in the lithium layer, it is considered that no uneven reaction occurs and the initial resistance does not become high.

[0010] In addition, the broadening of the base of the peak of the 1 / 20th width represents defects in the crystal structure of the lithium nickel cobalt manganese-containing composite oxide, and the broadening of the base means that the defects in the crystal structure are greater. On the other hand, the 1 / 20th width is affected by the half-width. Therefore, formula (2) is defined as an index representing the value of the 1 / 20th width after removing the influence of the half-width. Since the crystal structure of the lithium nickel cobalt manganese-containing composite oxide that satisfies formula (2) has small defects, it is considered that durability is improved and the increase in resistance is suppressed even when the charge and discharge are repeated. In addition, since the defects in the crystal structure are small, it is considered that no uneven reaction occurs and the initial resistance is not high. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram of a lithium ion battery according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram of an electrode assembly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present disclosure will be described, however, the present disclosure is not limited thereto.

[0013] In this specification, the expression "consisting essentially of" indicates that additional components may be included in addition to the essential components, as long as the purpose of the present disclosure is not impaired. For example, components normally expected in the field of the technology (e.g., inevitable impurities, etc.) may be included as additional components.

[0014] In this specification, when a compound is expressed by a stoichiometric composition formula such as "LiCoO2", the stoichiometric composition formula is merely a representative example. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to a composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. The composition ratio may be non-stoichiometric.

[0015] <Cathode active material> The positive electrode active material of this embodiment is a positive electrode active material for a lithium ion battery made of a lithium nickel cobalt manganese-containing composite oxide (hereinafter also referred to as "lithium composite oxide"). The lithium ion battery will be described in detail later. The positive electrode active material is a particle. The positive electrode active material can have any size. The positive electrode active material may have a D50 of, for example, 1 μm or more and 30 μm or less, or may have a D50 of 5 μm or more and 20 μm or less. In this specification, "D50" is defined as the particle size at which the cumulative frequency from the smallest particle size becomes 50% in the volume-based particle size distribution. The volume-based particle size distribution can be measured by a laser diffraction particle size distribution measuring device.

[0016] 《Particle structure》 The positive electrode active material includes secondary particles formed by agglomeration of a plurality of primary particles. The positive electrode active material may be, for example, substantially composed of secondary particles. The secondary particles are formed by agglomeration of 50 or more primary particles. The number of primary particles contained in the secondary particles is measured in a scanning electron microscope (SEM) image of the secondary particles. The magnification of the SEM image may be, for example, 10,000 to 30,000 times. The secondary particles may be formed by agglomeration of 100 or more primary particles. There is no upper limit to the number of primary particles in the secondary particles. The secondary particles may be formed by agglomeration of 10,000 or less primary particles. The secondary particles may be formed by agglomeration of 1,000 or less primary particles. The primary particles may have any shape. The primary particles may be, for example, spherical, columnar, or lumpy.

[0017] "composition" The positive electrode active material can reversibly absorb and release lithium ions. The positive electrode active material can have any crystal structure. The positive electrode active material can have, for example, a layered rock salt structure, a spinel structure, an olivine structure, or the like. The positive electrode active material can have any chemical composition. The chemical composition of the positive electrode active material can be measured, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0018] The positive electrode active material is made of a lithium nickel cobalt manganese-containing composite oxide. That is, the positive electrode active material is widely applicable to ternary positive electrode active materials containing at least nickel, cobalt, and manganese as transition metals, and the composition is not particularly limited.

[0019] However, the lithium nickel cobalt manganese-containing composite oxide of the present disclosure preferably has a composition represented by the following formula (i).

[0020] Li z Ni 1-x-y Co x Mn y O2(i) In the above formula (1), "x" satisfies the relationship "0.1≦x≦0.4", "y" satisfies the relationship "0.1≦y≦0.5", and "z" satisfies the relationship "0.95≦z≦1.2".

[0021] X-ray diffraction The positive electrode active material satisfies the relationships of the following formulas (1) and (2).

[0022] (18.768-a) / b≦0.0024 (1) c / d≦2.66 (2) In the above formula (1), "a" is the peak top of the (003) plane measured by X-ray diffraction of the positive electrode active material, and is in the range of a<18.768. "b" is the number of moles of manganese relative to the total number of moles of nickel, cobalt, and manganese in the positive electrode active material, and is represented by the following formula (3).

[0023] b = 100 × moles of manganese [mol] / (moles of nickel [mol] + moles of cobalt [mol] + moles of manganese [mol]) (3) In the above formula (2), "c" is 1 / 20th the width of the above "a", and "d" is the half width of the above "a".

[0024] When the positive electrode active material satisfies the relationships of the above formulas (1) and (2), the initial resistance can be reduced and an increase in resistance during repeated charge and discharge can be suppressed.

[0025] Here, the X-ray diffraction measurement may be, for example, a powder X-ray diffraction measurement using CuKα rays. This may be performed by making the X-rays (CuKα rays) irradiated from the X-ray source incident on the sample surface of the sample. The sample surface may be a surface composed of the positive electrode active material (typically a powder), or may be a surface where the positive electrode active material is bound with a binder to actually form the positive electrode (the surface of the positive electrode active material layer). Then, the angular difference (diffraction angle 2θ) between the diffraction direction and the incident direction of the X-rays and the diffracted X-ray intensity are measured, and from the obtained diffraction pattern, the half-width and the 1 / 20 width of the diffraction peak derived from the (003) plane can be calculated. Such X-ray diffraction measurement and the calculation of the half-width and the 1 / 20 width of the (003) plane can be performed using an X-ray diffraction measurement device commercially available from various measurement device manufacturers and the attached analysis software.

[0026] (Equation (1)) Regarding the value of a, the closer the value of a is to 18.768, the more uniformly the transition metals (nickel, cobalt, and manganese) are dispersed in the transition metal (nickel, cobalt, and manganese) layer in the crystal structure of the lithium nickel cobalt manganese-containing composite oxide, and since the occupancy rate of lithium in the lithium layer is high, the durability performance is improved and the increase in resistance is suppressed even when charge and discharge are repeated. The value of a is in the range of a < 18.768, preferably in the range of 18.68 < a < 18.768, and more preferably in the range of 18.7 < a < 18.768.

[0027] On the other hand, the inventors have found that since the value of a is affected by the composition ratio of the transition metals, particularly the composition ratio of manganese, it is necessary to satisfy the relationship of the above formula (1) regarding the values of a and b. In the above formula (1), the value of (18.768 - a) / b is preferably 0.0022 or less.

[0028] (Equation (2)) Regarding the value of c, the broadening of the base of the peak having a width 1 / 20 of the value of a represents defects in the crystal structure of the lithium composite oxide, and the larger the value of c, the larger the defects in the crystal structure. The value of c is preferably 0.32 or less, and more preferably 0.3 or less.

[0029] On the other hand, the present inventors have found that since the value of c is affected by the value of d, i.e., the half-width of the value of a, it is necessary for the values ​​of c and d to satisfy the relationship of the above formula (2). In the above formula (2), the value of c / d is preferably 2.60 or less.

[0030] 《Void》 In the positive electrode active material, the secondary particles may have a core portion having a void. The void is caused by the gap between the primary particles, and is preferably large. The secondary particles having a large void have a large outer surface area, and the number of primary particles present inside the secondary particles is small, so that the ratio of the primary particles that can contact the conductive material increases, and as a result, the initial resistance can be further reduced. In the present disclosure, the maximum diameter of the void is preferably, for example, 200 nm or more. In addition, in the positive electrode active material, it is more preferable that the ratio of the secondary particles having such voids with a maximum diameter of 200 nm or more inside is high, and for example, it is more preferable that the ratio is 50% or more.

[0031] The maximum diameter of the voids in the secondary particles and the ratio of secondary particles having voids with a maximum diameter of 200 nm or more inside can be calculated, for example, by the following method. First, a plurality of positive electrode active materials are embedded in a resin or the like, cut using a cross-section polisher (CP) to enable cross-sectional observation of the secondary particles, and then images are obtained using a SEM. The observation magnification is, for example, 8000 times. From the obtained images, 100 secondary particles that show the entirety of the particles are selected, and the maximum diameter of the voids in each particle is measured. The secondary particles whose maximum diameter is 200 nm or more are counted, and the ratio is calculated.

[0032] Shell section In the positive electrode active material, the secondary particles may further include a shell portion on the outside of the core portion and electrically connected to the core portion. When the secondary particles include the shell portion, the electronic conductivity is improved and the initial resistance can be further reduced. From the viewpoint of electronic conductivity, the thickness of the shell portion is preferably small. In the present disclosure, the thickness of the shell portion is, for example, preferably 0.9 μm or less, more preferably 0.6 μm or less.

[0033] The shell portion and the thickness of the shell portion can be confirmed and calculated, for example, by the same method as that for the maximum diameter of the voids in the secondary particles and the proportion of secondary particles having voids with a maximum diameter of 200 nm or more inside. However, in the present disclosure, the thickness of the shell portion is determined by measuring the thickness of each shell portion at two points for secondary particles whose maximum diameter of the voids in the secondary particles measured by the above-mentioned method is 200 nm or more, and averaging all the values.

[0034] <Method of manufacturing positive electrode active material> The method for producing a positive electrode active material according to the present embodiment includes at least a precursor preparation step (S10), a mixing step (S20), and a firing step (S30). The method may further include a precursor growth step between the precursor preparation step (S10) and the mixing step (S20), and a crushing step after the firing step (S30).

[0035] <Precursor preparation process (S10)> In the precursor preparation step, a precursor (composite hydroxide particles) containing nickel salt, cobalt salt, and manganese salt is prepared. The precursor is prepared, for example, by dissolving nickel salt, cobalt salt, and manganese salt in water in a predetermined ratio to prepare a raw material aqueous solution, adjusting the pH of the raw material aqueous solution, and then drying it.

[0036] The nickel salt is not particularly limited, but for example, nickel sulfate, nickel nitrate, nickel chloride, etc. can be used. The cobalt salt is not particularly limited, but for example, cobalt sulfate, cobalt nitrate, cobalt chloride, etc. can be used. The manganese salt is not particularly limited, but for example, manganese sulfate, manganese nitrate, manganese chloride, etc. can be used.

[0037] The nickel salt, the cobalt salt, and the manganese salt may be mixed, for example, so that the molar ratio of nickel, cobalt, and manganese is "(1-xy):x:y". "x" and "y" may satisfy, for example, the relationship of "0.1≦x≦0.4" and "0.1≦y≦0.5". By adjusting the concentration of the raw material aqueous solution containing the nickel salt, the cobalt salt, and the manganese salt, secondary particles having the desired values ​​of the above formulas (1) and (2) can be produced.

[0038] A reaction tank is prepared. The reaction tank may include an agitator, a heater, a temperature controller, and the like. In the reaction tank, water, an ammonium ion donor, and a pH adjuster are mixed to prepare an alkaline aqueous solution. The temperature of the alkaline aqueous solution is adjusted to, for example, 20° C. or more and 30° C. or less. The ammonia concentration of the alkaline aqueous solution is adjusted to, for example, 10 g / L or more and 20 g / L or less. The pH of the alkaline aqueous solution (measured at 25° C.) is adjusted to, for example, within a range of 11 to 13.

[0039] The ammonium ion donor is not particularly limited, but for example, ammonia water, an aqueous solution of ammonium sulfate, etc., can be used. The pH adjuster is not particularly limited, but for example, sodium hydroxide, potassium hydroxide, etc. can be used.

[0040] The raw aqueous solution is dropped into the alkaline aqueous solution while the alkaline aqueous solution in the reaction tank is stirred by a stirrer. During the dropping of the raw aqueous solution, heating and addition of an ammonium ion donor and a pH adjuster are appropriately performed so that the temperature of the reaction solution, the ammonia concentration of the reaction solution, and the pH of the reaction solution do not change significantly. The temperature of the reaction solution is adjusted to, for example, 20°C or higher and 30°C or lower. The ammonia concentration of the reaction solution is adjusted to, for example, 10 g / L or higher and 20 g / L or lower. The pH of the reaction solution (measured at 25°C) is adjusted to, for example, within a range of 11 or higher and 13 or lower. When the pH of the reaction solution is within the above range, secondary particles having desired voids can be produced.

[0041] The precursor-containing aqueous solution after the above-mentioned reaction is dried to prepare the precursor. 《Mixing process (S20)》 In the mixing step, the precursor obtained in the precursor preparation step is mixed with a lithium salt to prepare a lithium mixture. The lithium salt is not particularly limited, but for example, lithium carbonate, lithium hydroxide, lithium nitrate, etc. can be used.

[0042] In the mixing step, the precursor and the lithium salt may be mixed so that the ratio of the number of lithium atoms in the lithium mixture to the sum of the number of nickel, cobalt and manganese atoms is, for example, in the range of 1.1 to 1.5. When the ratio of the number of lithium atoms in the lithium mixture to the sum of the number of nickel, cobalt and manganese atoms is in the range of 1.1 to 1.5, secondary particles having desired values ​​for the above formulas (1) and (2) can be produced. It is preferable to adjust the ratio of the number of lithium atoms in the lithium mixture to the sum of the number of nickel, cobalt and manganese atoms to be in the range of 1.1 to 1.3. A general mixer can be used for mixing.

[0043] Firing process (S30) In the firing step, the lithium mixture obtained in the mixing step is fired to produce a lithium composite oxide.

[0044] The firing temperature is 750°C or more and 950°C or less. If the firing temperature is less than 750°C, the lithium and the precursor do not react sufficiently, and excess lithium or unreacted precursor may remain, or the crystallinity of the resulting lithium composite oxide may be insufficient. If the firing temperature exceeds 950°C, the outer surface area of ​​the resulting lithium composite oxide may decrease, or the secondary particles of the lithium composite oxide may abnormally sinter, resulting in an increase in amorphous secondary particles. The firing temperature is preferably 800°C or more and 900°C or less.

[0045] The heating rate is 0.3° C. / min or more and less than 5° C. / min. When the heating rate is within the above range, the reaction between lithium and the precursor does not become uneven, and the crystallinity of the resulting lithium composite oxide is stable. The heating rate is preferably 0.5° C. / min or more and less than 2° C. / min.

[0046] The firing time is 2 hours or more and 24 hours or less. If the firing time is less than 2 hours, the lithium and the precursor do not react sufficiently, and excess lithium or unreacted precursor may remain, or the crystallinity of the resulting lithium composite oxide may be insufficient. If the firing temperature exceeds 24 hours, the outer surface area of ​​the resulting lithium composite oxide may decrease, or the secondary particles of the lithium composite oxide may abnormally sinter, resulting in an increase in amorphous secondary particles. The firing time is preferably 5 hours or more and 18 hours or less. Note that the firing time in this disclosure refers to the time from when the maximum temperature is reached after the start of heating until the maximum temperature is reached and the time until cooling to room temperature (30°C) after heating at the maximum temperature is completed (cooling time).

[0047] For example, dry air, an oxygen atmosphere, an inert atmosphere, etc., can be used for the calcination, but an oxygen atmosphere is preferred. The oxygen concentration of the oxygen atmosphere is preferably 20% by volume or more and 100% by volume or less, and more preferably 50% by volume or more and 100% by volume or less. If the oxygen concentration of the oxygen atmosphere is less than 20% by volume, the crystallinity of the resulting lithium composite oxide may be insufficient.

[0048] 《Precursor growth process》 In this embodiment, a precursor growing step may be further provided between the precursor producing step and the mixing step. In the precursor growing step, the precursor obtained in the precursor producing step is grown.

[0049] After the precursor preparation step is completed, the pH (measured at 25° C.) of the precursor-containing aqueous solution in the reaction tank is adjusted to be lower than the pH in the precursor preparation step to prepare an aqueous solution for precursor growth. The pH of the aqueous solution for precursor growth is adjusted, for example, by changing the amount of a pH adjuster added.

[0050] After adjusting the pH of the precursor growth aqueous solution, heating and addition of an ammonium ion donor and a pH adjuster are appropriately performed while stirring the precursor growth aqueous solution so that the temperature, ammonia concentration, and pH of the precursor growth aqueous solution do not change significantly. The temperature of the precursor growth aqueous solution is adjusted to, for example, 20° C. or higher and 30° C. or lower. The ammonia concentration of the precursor growth aqueous solution is adjusted to, for example, 10 g / L or higher and 20 g / L or lower. The pH of the precursor growth aqueous solution (measured at 25° C.) is adjusted to, for example, within a range of 10.5 or higher and 12 or lower. When the pH of the precursor growth aqueous solution is within the above range, secondary particles having larger voids can be produced.

[0051] 《Crushing process》 In this embodiment, a crushing step may be further provided after the firing step, because the lithium composite oxide obtained by the firing step is in the form of secondary particles, and may be aggregated or sintered.

[0052] The crushing method can be a conventionally known method, for example, a mortar, a ball mill, a hammer mill, etc. can be used.

[0053] <Lithium-ion battery> The lithium ion battery of the present embodiment will be described below. The lithium ion battery of the present embodiment may be a secondary battery. The lithium ion battery of the present embodiment may be a primary battery. Hereinafter, the lithium ion battery may be abbreviated to "battery".

[0054] <Lithium-ion battery> FIG. 1 is a schematic diagram of a lithium ion battery according to the present embodiment. Hereinafter, the "lithium ion battery according to the present embodiment" may be abbreviated as "the present battery." The present battery 100 includes a case 90. The case 90 may be made of metal, for example. The case 90 may have any shape. The case 90 may be, for example, rectangular (flattened rectangular parallelepiped) or cylindrical. The case 90 may be, for example, a pouch made of an Al laminate film. The case 90 may be provided with a positive terminal 91 and a negative terminal 92.

[0055] The case 90 houses the electrode assembly 50 and an electrolyte. The electrolyte is impregnated into the electrode assembly 50. A portion of the electrolyte may be stored in the bottom of the case 90. The electrode assembly 50 is connected to a positive electrode terminal 91 and a negative electrode terminal 92.

[0056] FIG. 2 is a schematic diagram of an electrode body. The electrode body 50 includes a positive electrode 10, a separator 30, and a negative electrode 20. The electrode body 50 may have any structure. The electrode body 50 may be, for example, a wound type. The electrode body 50 may include, for example, a laminate 40. The laminate 40 is formed by laminating a positive electrode 10, a separator 30 (first sheet), a negative electrode 20, and a separator 30 (second sheet) in this order. The laminate 40 is wound in a spiral shape to form the electrode body 50. After winding, the electrode body 50 may be formed into a flat shape.

[0057] 《Positive electrode》 The positive electrode 10 may be, for example, a strip-shaped sheet. The positive electrode 10 may include a positive electrode collector and a positive electrode active material layer. The positive electrode collector may include, for example, Al foil or the like. The positive electrode active material layer may be disposed on the surface of the positive electrode collector. The positive electrode active material layer may be disposed on only one side of the positive electrode collector, or may be disposed on both the front and back sides. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material layer may further include, for example, a conductive material, a binder, and the like.

[0058] The conductive material may include, for example, carbon black (e.g., acetylene black, etc.), carbon fiber, etc. The amount of the conductive material may be, for example, 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the positive electrode active material. The binder may include, for example, polyvinylidene fluoride (PVDF), etc. The amount of the binder may be, for example, 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the positive electrode active material.

[0059] 《Negative electrode》 The negative electrode 20 may be, for example, a strip-shaped sheet. The negative electrode 20 may include a negative electrode current collector and a negative electrode active material layer. The negative electrode current collector may include, for example, Cu foil or the like. The negative electrode active material layer may be disposed on the surface of the negative electrode current collector. The negative electrode active material layer may be disposed on only one side of the negative electrode current collector, or may be disposed on both the front and back sides. The negative electrode active material layer includes a negative electrode active material. The negative electrode active material layer may further include, for example, a conductive material, a binder, and the like.

[0060] The negative electrode active material is typically a particle group. The negative electrode active material may have a D50 of, for example, 1 μm or more and 30 μm or less. The negative electrode active material absorbs and releases lithium ions. The negative electrode active material should not be particularly limited. The negative electrode active material may be, for example, graphite (e.g., amorphous coated graphite, etc.), graphitizable carbon, non-graphitizable carbon, silicon, silicon oxide, silicon-based alloy, tin, tin oxide, tin-based alloy, lithium (pure metal), lithium alloy (e.g., Li-Al alloy, etc.), lithium titanate, etc. The negative electrode 20 may contain one type of negative electrode active material alone. The negative electrode 20 may contain two or more types of negative electrode active materials.

[0061] The conductive material may include, for example, carbon nanotubes (CNTs) or the like. The amount of the conductive material may be, for example, 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the negative electrode active material. The binder may include, for example, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), or the like. The amount of the binder may be, for example, 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the negative electrode active material.

[0062] <Separator> The separator 30 may be, for example, a strip-shaped film. The separator 30 is porous. The separator 30 is permeable to an electrolyte. The separator 30 separates the positive electrode 10 and the negative electrode 20. The separator 30 is electrically insulating. The separator 30 may contain, for example, a polyolefin resin. The polyolefin resin may contain, for example, at least one selected from the group consisting of polyethylene (PE) and polypropylene (PP). The separator 30 may have, for example, a single-layer structure. The separator 30 may be, for example, substantially composed of a PE layer. The separator 30 may have, for example, a multi-layer structure. The separator may be formed by laminating, for example, a PP layer, a PE layer, and a PP layer in this order. For example, a heat-resistant layer (ceramic particle layer) or the like may be formed on the surface of the separator 30.

[0063] 《Electrolyte》 The electrolyte includes a solvent and a lithium salt. The solvent is aprotic. The solvent may include any component. The solvent may include at least one selected from the group consisting of, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), 1,2-dimethoxyethane (DME), methyl formate (MF), methyl acetate (MA), methyl propionate (MP), and γ-butyrolactone (GBL).

[0064] The lithium salt is a supporting electrolyte. The lithium salt is dissolved in a solvent. The lithium salt may include at least one selected from the group consisting of LiPF6, LiBF4, and LiN(FSO2)2. The lithium salt may have a molar concentration of, for example, 0.5 mol / L or more and 2.0 mol / L or less, or may have a molar concentration of 0.8 mol / L or more and 1.2 mol / L or less.

[0065] The electrolyte may further contain any additive in addition to the solvent and the lithium salt. For example, the electrolyte may contain an additive in a mass fraction of 0.01% or more and 5% or less. The additive may contain at least one selected from the group consisting of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like. EXAMPLES

[0066] The present embodiment will be described below using examples, but the present embodiment is not limited to these.

[0067] <Example 1> <Production of Positive Electrode Active Material> (Precursor preparation process) Nickel sulfate, cobalt sulfate and manganese sulfate were dissolved in water to obtain a raw solution. The molar ratios of nickel, cobalt and manganese in the raw solution and the total molar concentration of nickel, cobalt and manganese in the raw solution are shown in Table 1.

[0068] A reaction tank was prepared. The reaction tank was equipped with a stirrer, a heater, and a temperature controller. In the reaction tank, an alkaline aqueous solution was prepared by supplying an appropriate amount of 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution to 0.8 L of water. The temperature of the alkaline aqueous solution was adjusted to 25°C. The ammonia concentration of the alkaline aqueous solution was 12.5 g / L. The pH of the alkaline aqueous solution was adjusted to 11.4.

[0069] The raw material aqueous solution was added dropwise to the alkaline aqueous solution while the alkaline aqueous solution in the reaction tank was stirred by a stirrer. During the dropwise addition of the raw material aqueous solution, the temperature of the reaction solution was adjusted to 25°C. During the dropwise addition of the raw material aqueous solution, ammonia water was appropriately added so that the ammonia concentration of the reaction solution was maintained at 12.5 g / L. Sodium hydroxide aqueous solution was appropriately added so that the pH of the reaction solution was 11.4. After the reaction, the precursor-containing aqueous solution was dried to obtain the precursor.

[0070] (Mixing process) The precursor was mixed with lithium carbonate to obtain a lithium mixture, in which the ratio of the number of lithium atoms to the sum of the numbers of nickel, cobalt, and manganese atoms was as shown in Table 1.

[0071] (Firing process) The lithium mixture was fired at the firing temperature, heating rate, firing time and oxygen concentration shown in Table 1 to obtain a lithium composite oxide.

[0072] (Crushing process) The lithium composite oxide was crushed in a mortar to obtain the lithium composite oxide of Example 1 (positive electrode active material).

[0073] <Comparative Example 1> (Precursor preparation process) A raw material aqueous solution was obtained in the same manner as in Example 1. The molar ratios of nickel, cobalt, and manganese in the raw material aqueous solution and the total molar concentration of nickel, cobalt, and manganese in the raw material aqueous solution are as shown in Table 1. Next, a precursor was obtained in the same manner as in Example 1.

[0074] (Mixing process) A lithium mixture was obtained in the same manner as in Example 1. In the lithium mixture, the ratio of the number of lithium atoms to the sum of the numbers of nickel, cobalt and manganese atoms is as shown in Table 1.

[0075] (Firing process) The lithium mixture was fired at the firing temperature, heating rate, firing time and oxygen concentration shown in Table 1 to obtain a lithium composite oxide.

[0076] (Crushing process) The lithium composite oxide was crushed in the same manner as in Example 1 to obtain a lithium composite oxide (positive electrode active material) of Comparative Example 1.

[0077] <Examples 2 to 6, Comparative Examples 2 to 3> (Precursor preparation process) A raw material aqueous solution was obtained in the same manner as in Example 1. The molar ratios of nickel, cobalt, and manganese in each raw material aqueous solution and the total molar concentration of nickel, cobalt, and manganese in each raw material aqueous solution are as shown in Table 1. Next, each precursor-containing aqueous solution was obtained in the same manner as in Example 1. The pH of each precursor-containing aqueous solution was adjusted to 12.5.

[0078] (Precursor growth process) In the precursor-containing aqueous solution, the pH was adjusted by adjusting the amount of sodium hydroxide aqueous solution to be supplied, and an aqueous solution for precursor growth was obtained. The pH of each aqueous solution for precursor growth is as shown in Table 1. After adjusting the pH of the aqueous solution for precursor growth, the aqueous solution for precursor growth was stirred. During stirring of the aqueous solution for precursor growth, the temperature of the aqueous solution for precursor growth was adjusted to 25°C. During stirring of the aqueous solution for precursor growth, ammonia water was appropriately added so that the ammonia concentration of the aqueous solution for precursor growth was maintained at 12.5 g / L. During stirring of the aqueous solution for precursor growth, sodium hydroxide aqueous solution was appropriately added so that the pH of the aqueous solution for precursor growth became each pH shown in Table 1. After the reaction, the aqueous solution for precursor growth was dried to obtain each precursor.

[0079] (Mixing process) The precursor and lithium carbonate were mixed to obtain lithium mixtures. In each lithium mixture, the ratio of the number of lithium atoms to the sum of the numbers of nickel, cobalt, and manganese atoms is as shown in Table 1.

[0080] (Firing process) Each lithium mixture was fired at the firing temperature, heating rate, firing time and oxygen concentration shown in Table 1 to obtain each lithium composite oxide.

[0081] (Crushing process) Each lithium composite oxide was crushed in the same manner as in Example 1 to obtain the lithium composite oxides (positive electrode active materials) of Examples 2 to 6 and Comparative Examples 2 to 3.

[0082] <Production of lithium-ion batteries> As the positive electrode materials, the positive electrode active materials of Examples 1 to 6 and Comparative Examples 1 to 3, acetylene black (Denka Co., Ltd.) as a conductive material, PVDF (Kureha Co., Ltd.) as a binder, and Al foil (thickness: 15 μm) as a positive electrode current collector were prepared. A positive electrode was produced from the above materials.

[0083] The negative electrode was made of the following materials: natural graphite (Hitachi Chemical Co., Ltd.) as the negative electrode active material, CMC (Nippon Paper Industries Co., Ltd.) and SBR (JSR Corporation) as the binder, and Cu foil (thickness: 10 μm) as the negative electrode current collector.

[0084] A porous resin (PP / PE / PP) (thickness: 24 μm) in which a PP layer was laminated on both sides of a PE layer was prepared as a separator. The positive electrode, separator, and negative electrode were laminated so that the separator separated the positive electrode and the negative electrode. This formed an electrode body.

[0085] A pouch made of a laminate film was prepared as the exterior body. An electrode body was housed in the exterior body. A non-aqueous electrolyte solution was used in which a supporting salt (LiPF6) was dissolved at a concentration of 1 mol / L in a mixed solvent containing EC, DMC, and EMC. The electrolyte solution was injected into the exterior body. After the electrolyte solution was injected, the exterior body was sealed. As described above, the test batteries (pouch-type lithium ion batteries) of Examples 1 to 6 and Comparative Examples 1 to 3 were manufactured.

[0086] [Table 1]

[0087] <Analysis> "composition" The compositions of the positive electrode active materials of Examples 1 to 6 and Comparative Examples 1 to 3 were confirmed by an ICP optical emission spectrometer (PS3520UVDD, manufactured by Hitachi High-Tech Science Corporation). The compositions of the positive electrode active materials are shown in Table 2.

[0088] X-ray diffraction The positive electrode active materials of Examples 1 to 6 and Comparative Examples 1 to 3 were irradiated with X-rays using an X-ray diffractometer (Smartlab, manufactured by Rigaku Corporation) under the following measurement conditions to obtain X-ray diffraction patterns. From the obtained X-ray diffraction patterns, the peak top (a) of the (003) plane, the 1 / 20th width of the peak top (b), and the half width of the peak top (c) were calculated to determine the values ​​of formulas (1) and (2). The results are shown in Table 2.

[0089] [Measurement conditions] X-ray output: 45kV, 200mA X-ray source: CuKα radiation (wavelength: 1.54051 Å), single crystal monochromator Diffraction angle: 10~120° Measurement temperature: room temperature Scanning speed: 1 second / step 《Void》 A part of the positive electrode active material of Examples 1 to 6 and Comparative Examples 1 to 3 was embedded in a resin, cut using a CP, and made into a state in which the cross section of the secondary particles could be observed, and then images were obtained by SEM at an observation magnification of 8000 times. From the obtained images, 100 pieces in which the entire secondary particles were shown were selected, the maximum diameter of the voids in each particle was measured, and the number of secondary particles in which the maximum diameter of the voids in the secondary particles was 200 nm or more was counted, and the proportion was calculated. The results are shown in Table 2.

[0090] <Shell thickness> The presence or absence of a shell portion was confirmed for secondary particles whose maximum void diameter was 200 nm or more, as measured by the above-mentioned method. 50 secondary particles in which a shell portion was confirmed were selected, and the thickness of the shell portion of each secondary particle was measured at two points, and the average value of the 50 secondary particles was taken as the shell thickness. The results are shown in Table 2.

[0091] <Evaluation> 《Initial resistance》 The SOC (State of Charge) of the test battery was adjusted to 50% by constant current-constant voltage (CC-CV) charging in a temperature environment of 25°C. The current during constant current (CC) charging was 1 It. "1 It" is defined as the current that drains the rated capacity of the battery in 1 hour. At 50% SOC, the battery voltage was 3.7V. After adjusting the SOC, the battery was discharged for 10 seconds at a current of 10 It with a 30-minute break in between. The initial discharge resistance (initial resistance) was calculated by the following formula (4). The results are shown in Table 2. The initial resistance in Table 2 is a relative value. The initial resistance of Comparative Example 1 is defined as 1.

[0092] r = (V0 - V 10 ) / current formula (4) In the above formula (4), r represents the discharge resistance. V0 represents the voltage at the start of discharge. 10 indicates the voltage 10 seconds after the start of discharge.

[0093] Resistance Increase Rate After measuring the initial resistance, the SOC of the battery was adjusted to 80% by CC-CV charging in a temperature environment of 25°C. The current during CC charging was 1 It. After adjusting the SOC, a cycle test was carried out in a temperature environment of 25°C. That is, the following discharge and charge were alternately repeated for 15 days.

[0094] Discharge: Current = 1 It, Discharge capacity = Capacity equivalent to 20% SOC Charging: Current = 1It, Charge capacity = Capacity equivalent to 20% SOC After the cycle test, the discharge resistance after the cycle (resistance after cycling) was measured in the same manner as the initial resistance. The resistance increase rate (percentage) was calculated by dividing the resistance after cycling by the initial resistance. The results are shown in Table 2.

[0095] [Table 2]

[0096] <Result> As shown in Table 2, in this embodiment, when formulas (1) and (2) are satisfied, the initial resistance and the resistance increase rate are low. In addition, it is found that the initial resistance is lowered when the ratio of the secondary particles having a maximum void diameter of 200 nm or more in the positive electrode active material is high. It is also found that the initial resistance is lowered when the thickness of the shell part is reduced.

[0097] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is defined by the claims, not the above description, and is intended to include all modifications within the scope and meaning equivalent to the claims. [Explanation of symbols]

[0098] 10 positive electrode, 20 negative electrode, 30 separator, 40 laminate, 50 electrode body, 90 case, 91 positive electrode terminal, 92 negative electrode terminal, 100 lithium ion battery.

Claims

1. A positive electrode active material for a lithium ion battery, comprising a lithium nickel cobalt manganese-containing composite oxide, The positive electrode active material includes secondary particles formed by agglomeration of a plurality of primary particles, The positive electrode active material has the formula (1): (18.768-a) / b≦0.0022 (1) and formula (2): c / d≦2.66 (2) Fulfilling the relationship, In the formula (1), a is the peak top of the (003) plane measured by X-ray diffraction of the positive electrode active material, and is in the range of 18.7<a<18.768; b is the percentage of the number of moles of manganese relative to the total number of moles of nickel, cobalt, and manganese in the positive electrode active material, In the formula (2), c is 1 / 20th the width of a, d is the half width of the a, The secondary particles have a core portion having a void, The ratio of the secondary particles having the voids with a maximum diameter of 200 nm or more is 50% or more. Cathode active material.

2. The secondary particle has a shell portion outside the core portion, The thickness of the shell portion is 0.9 μm or less. The positive electrode active material according to claim 1 .

Citation Information

Patent Citations

  • Spherical or spheroidal lithium ion battery positive electrode material and lithium ion battery

    JP2019021626A

  • Positive electrode active material for lithium ion secondary battery, and method for manufacturing the same

    JP2020107536A

  • Positive electrode active material for lithium ion secondary battery and lithium ion secondary battery

    JP2021051880A